2016
DOI: 10.1155/2016/1461648
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Potential of Mesenchymal Stromal Cells: Age‐Related Changes

Abstract: Preclinical and clinical studies have shown that a therapeutic effect results from mesenchymal stromal cells (MSCs) transplant. No systematic information is currently available regarding whether donor age modifies MSC regenerative potential on cutaneous wound healing. Here, we evaluate whether donor age influences this potential. Two different doses of bone marrow MSCs (BM-MSCs) from young, adult, or old mouse donors or two doses of their acellular derivatives mesenchymal stromal cells (acd-MSCs) were intrader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 44 publications
4
26
0
Order By: Relevance
“…We conclude that PDLSCs from individuals of different age groups impart strong immunosuppressive effects on the proliferation of allogeneic PBMCs, whether in cell-cell contact culture or Transwell cultures, whereas the immunosuppressive effect of PDLSCs from adult individuals was weaker than that of PDLSCs from young subjects. These ndings agree with the results of previous reports using other kinds of MSCs, i.e., donor age in uences immunoregulation in MSCs (14,33,34), although MSC inhibition of T cell proliferation is preserved in the elderly (35). Furthermore, we found that the difference in immunosuppressive ability between APDLSCs and YPDLSCs is not related to the apoptosis of PBMCs.…”
Section: Discussionsupporting
confidence: 92%
“…We conclude that PDLSCs from individuals of different age groups impart strong immunosuppressive effects on the proliferation of allogeneic PBMCs, whether in cell-cell contact culture or Transwell cultures, whereas the immunosuppressive effect of PDLSCs from adult individuals was weaker than that of PDLSCs from young subjects. These ndings agree with the results of previous reports using other kinds of MSCs, i.e., donor age in uences immunoregulation in MSCs (14,33,34), although MSC inhibition of T cell proliferation is preserved in the elderly (35). Furthermore, we found that the difference in immunosuppressive ability between APDLSCs and YPDLSCs is not related to the apoptosis of PBMCs.…”
Section: Discussionsupporting
confidence: 92%
“…These studies indicate that wounds treated with MSCs show a qualitative improvement in histological characteristics. Specifically, they report superior rete ridge architecture, multi-layered structure, improved dermal-epidermal junction and the formation of new skin appendage structures, such as hair follicles and sebaceous glands [ 22 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Arango et al conducted a study to elucidate the role of MSC acellular derivatives on wound healing using different animal models, in particular, a diabetic mouse model. The results revealed that the wounds treated with the derivatives improved the synthesis, deposition and organization of collagen fibers at the dermal matrix, relative to the wounds treated with MSCs only [124,176]. Another recent study showed that the intravenous injection of acellular derivatives promoted cutaneous wound repair when exosomes secreted by human AD-MSCs (AD-Exos) were administered in murine incisional wounds.…”
Section: Stimulation Of Proliferation and Migration Of Local Keratinomentioning
confidence: 99%